Digital Marketing Communication In Building The Image Of Local Cuisine Products @ter.dimsum.dimsum - Dema Guhaningtias; Siti Khumayah; Aghnia Dian Lestari (Ann Publisher, 2026)
Background. The development of digital technology has encouraged MSMEs to utilize social media as a primary marketing tool, particularly Instagram, which is visual and interactive. Aims. This study aims to analyze the digital marketing communication strategies on the Instagram account @ter.dimsum.dimsum in building the image of local culinary products. Methods. The method used is descriptive qualitative method, with data collection techniques of interviews with business owners, observation of Instagram content, and documentation. The data were analyzed through the stages of reduction, presentation, and drawing conclusions. Result. The results indicate that @ter.dimsum.dimsum primarily leverages visual content, simple narratives, and two-way interaction. From a digital marketing perspective, the